The Dynamics of Living Art Matrix - Sushma K. Bahl (International Journal of Arts Architecture & Design, 2023)
The essay explores India’s contemporary art matrix as a living cultural continuum. Drawing on sound philosophical principles of the classical, sacred and courtly traditions on the one hand, and linked to tribal-folk art/craft forms on the other, its multitude of interdisciplinary aesthetics are living expressions by living people. Some of the work in the varied genres of art matrix is created by professionally trained urban artists while other by their rural primarily family-trained counterparts. Both are innately contemporary as they draw inspiration from their roots, while opening up to their lived experiences, surroundings and evolving technologies. However, the dichotomy between the two remains a challenge. The essay makes a case for affinity and a shared platform on equal terms, space, credit and returns for the two distinct but interconnected and innately contemporary genres to eschew marginalisation and appropriation of the lesser or folk/tribal artists’ from subaltern India by their more market savvy urbane colleagues.